edits
[lambda.git] / week4.mdwn
1 [[!toc]]
2
3 #These notes return to the topic of fixed point combiantors for one more return to the topic of fixed point combinators#
4
5 Q: How do you know that every term in the untyped lambda calculus has
6 a fixed point?
7
8 A: That's easy: let `T` be an arbitrary term in the lambda calculus.  If
9 `T` has a fixed point, then there exists some `X` such that `X <~~>
10 TX` (that's what it means to *have* a fixed point).
11
12 <pre>
13 let W = \x.T(xx) in
14 let X = WW in
15 X = WW = (\x.T(xx))W = T(WW) = TX
16 </pre>
17
18 Q: How do you know that for any term T, YT is a fixed point of T?
19
20 A: Note that in the proof given in the previous answer, we chose `T`
21 and then set `X = WW = (\x.T(xx))(\x.T(xx))`.  If we abstract over
22 `T`, we get the Y combinator, `\T.(\x.T(xx))(\x.T(xx))`.  No matter
23 what argument `T` we feed Y, it returns some `X` that is a fixed point
24 of `T`, by the reasoning in the previous answer.
25
26 Q: So if every term has a fixed point, even Y has fixed point.
27
28 A: Right:
29
30     let Y = \T.(\x.T(xx))(\x.T(xx)) in
31     Y Y = \T.(\x.T(xx))(\x.T(xx)) Y
32         = (\x.Y(xx))(\x.Y(xx))
33         = Y((\x.Y(xx))(\x.Y(xx)))
34         = Y(Y((\x.Y(xx))(\x.Y(xx))))
35         = Y(Y(Y(...(Y(YY))...)))
36
37 Q: Ouch!  Stop hurting my brain.
38
39 A: Let's come at it from the direction of arithmetic.  Recall that we
40 claimed that even `succ`---the function that added one to any
41 number---had a fixed point.  How could there be an X such that X = X+1?
42 Then
43
44     X = succ X = succ (succ X) = succ (succ (succ (X))) = succ (... (succ X)...)
45
46 In other words, the fixed point of `succ` is a term that is its own
47 successor.  Let's just check that `X = succ X`:
48
49     let succ = \n s z. s (n s z) in
50     let X = (\x.succ(xx))(\x.succ(xx)) in
51     succ X 
52       = succ ((\x.succ(xx))(\x.succ(xx))) 
53       = succ (succ ((\x.succ(xx))(\x.succ(xx))))
54       = succ (succ X)
55
56 You should see the close similarity with YY here.
57
58 Q. So `Y` applied to `succ` returns infinity!
59
60 A. Yes!  Let's see why it makes sense to think of `Y succ` as a Church
61 numeral:
62
63       [same definitions]
64       succ X
65       = (\n s z. s (n s z)) X 
66       = \s z. s (X s z)
67       = succ (\s z. s (X s z)) ; using fixed-point reasoning
68       = \s z. s ([succ (\s z. s (X s z))] s z)
69       = \s z. s ([\s z. s ([succ (\s z. s (X s z))] s z)] s z)
70       = \s z. s (s (succ (\s z. s (X s z))))
71
72 So `succ X` looks like a numeral: it takes two arguments, `s` and `z`,
73 and returns a sequence of nested applications of `s`...
74
75 You should be able to prove that `add 2 (Y succ) <~~> Y succ`,
76 likewise for `mult`, `minus`, `pow`.  What happens if we try `minus (Y
77 succ)(Y succ)`?  What would you expect infinity minus infinity to be?
78 (Hint: choose your evaluation strategy so that you add two `s`s to the
79 first number for every `s` that you add to the second number.)
80
81 This is amazing, by the way: we're proving things about a term that
82 represents arithmetic infinity.  It's important to bear in mind the
83 simplest term in question is not infinite:
84
85      Y succ = (\f.(\x.f(xx))(\x.f(xx)))(\n s z. s (n s z))
86
87 The way that infinity enters into the picture is that this term has
88 no normal form: no matter how many times we perform beta reduction,
89 there will always be an opportunity for more beta reduction.  (Lather,
90 rinse, repeat!)
91
92 Q. That reminds me, what about [[evaluation order]]?
93
94 A. For a recursive function that has a well-behaved base case, such as
95 the factorial function, evaluation order is crucial.  In the following
96 computation, we will arrive at a normal form.  Watch for the moment at
97 which we have to make a choice about which beta reduction to perform
98 next: one choice leads to a normal form, the other choice leads to
99 endless reduction:
100
101     let prefac = \f n. isZero n 1 (mult n (f (pred n))) in
102     let fac = Y prefac in
103     fac 2
104        = [(\f.(\x.f(xx))(\x.f(xx))) prefac] 2
105        = [(\x.prefac(xx))(\x.prefac(xx))] 2
106        = [prefac((\x.prefac(xx))(\x.prefac(xx)))] 2
107        = [prefac(prefac((\x.prefac(xx))(\x.prefac(xx))))] 2
108        = [(\f n. isZero n 1 (mult n (f (pred n))))
109           (prefac((\x.prefac(xx))(\x.prefac(xx))))] 2
110        = [\n. isZero n 1 (mult n ([prefac((\x.prefac(xx))(\x.prefac(xx)))] (pred n)))] 2
111        = isZero 2 1 (mult 2 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] (pred 2)))
112        = mult 2 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] 1)
113        ...
114        = mult 2 (mult 1 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] 0))
115        = mult 2 (mult 1 (isZero 0 1 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] (pred 0))))
116        = mult 2 (mult 1 1)
117        = mult 2 1
118        = 2
119
120 The crucial step is the third from the last.  We have our choice of
121 either evaluating the test `isZero 0 1 ...`, which evaluates to `1`,
122 or we can evaluate the `Y` pump, `(\x.prefac(xx))(\x.prefac(xx))`, to
123 produce another copy of `prefac`.  If we postpone evaluting the
124 `isZero` test, we'll pump out copy after copy of `prefac`, and never
125 realize that we've bottomed out in the recursion.  But if we adopt a
126 leftmost/call by name/normal order evaluation strategy, we'll always
127 start with the isZero predicate, and only produce a fresh copy of
128 `prefac` if we are forced to. 
129
130 Q.  You claimed that the Ackerman function couldn't be implemented
131 using our primitive recursion techniques (such as the techniques that
132 allow us to define addition and multiplication).  But you haven't
133 shown that it is possible to define the Ackerman function using full
134 recursion.
135
136 A. OK:
137   
138 <pre>
139 A(m,n) =
140     | when m == 0 -> n + 1
141     | else when n == 0 -> A(m-1,1)
142     | else -> A(m-1, A(m,n-1))
143
144 let A = Y (\A m n. isZero m (succ n) (isZero n (A (pred m) 1) (A (pred m) (A m (pred n))))) in
145 </pre>
146
147 For instance,
148
149     A 1 2
150     = A 0 (A 1 1)
151     = A 0 (A 0 (A 1 0))
152     = A 0 (A 0 (A 0 1))
153     = A 0 (A 0 2)
154     = A 0 3
155     = 4
156
157 A 1 x is to A 0 x as addition is to the successor function;
158 A 2 x is to A 1 x as multiplication is to addition;
159 A 3 x is to A 2 x as exponentiation is to multiplication---
160 so A 4 x is to A 3 x as super-exponentiation is to exponentiation...
161